Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.60014/pmjg.v3i2.65
|View full text |Cite
|
Sign up to set email alerts
|

A Review of National Programme Data on the HIV Epidemic in Ghana: 2005-2010

Abstract: Introduction: Enormous national efforts have gone into combating the HIV epidemic in Ghana. This study reviewed data from the National AIDS/STI Control Programme over the period 2005-2010, in terms of time, place and person characteristics of the epidemic.It focused on past and current efforts at combating the epidemic and what future efforts are required.Methods: It was a descriptive review of data from HIV sentinel surveys (HSS) and annual reports of the National AIDS/STI Control Programme (NACP) from 2005 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Interestingly more working men were involved in activities which took them outside the community more often compared to women, and this has significance for HIV risk behaviours, testing experience and service provision. Studies have indicated that itinerant nature and frequent male mobility may require special HIV testing and service provision avenues 10,11,12 . In addition, previous research in Ghana have indicated that community based testing programmes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly more working men were involved in activities which took them outside the community more often compared to women, and this has significance for HIV risk behaviours, testing experience and service provision. Studies have indicated that itinerant nature and frequent male mobility may require special HIV testing and service provision avenues 10,11,12 . In addition, previous research in Ghana have indicated that community based testing programmes (i.e.…”
Section: Discussionmentioning
confidence: 99%